Effect of Supplementation of Azolla (Azolla carolini) Meal on Performance of Crossbred (Hampshire × Ghungroo) Pigs - Barman, Keshab; Konwar, Dipanjali (Indian Journal of Animal Nutrition, 2018)
Twelve crossbred (Hampshire x Ghungroo) grower pigs (about 3.5 months, 19.31 ±0.10 kg BW) of either sex were divided into three groups of six each in a randomized block design to study the effect of supplementation of Azolla (Azolla carolini) on production performance of crossbred pigs. The trial was conducted in two phases i.e. grower stage from 3-5 months of age and finisher stage from 5-8 months aged of the pigs. The treatment groups were T1G (control) and T2G (2 % Azolla) in grower stage and T1F (control) and T2F (2 % Azolla) in finisher stage. All the diets were iso-nitrogenous and iso caloric. Growth was found higher (P>0.05) in pigs of both the phase supplemented with Azolla with better (P>0.05) feed conversion ratio (FCR-3.63±0.35 in T2G and 3.97±0.25 in T2F; ) and lower (P>0.01) feeding cost (Rs 60.80±5.93 in T2G and 66.40±4.11 in T2F per kg gain). Digestibility of all the nutrients were found higher (P>0.05) in all the animals supplemented with Azolla meal (T2G and T2F). Average daily gain (g/d) was increased (P>0.05) by 2.75 % in grower phase (258.01±36.20 vs 265.13±28.10) and by 2.46 % in finisher phase (405.91±57.50 vs 415.90±60.60). Higher (P>0.05) average daily gain (ADG) with better (P>0.05) FCR and lower (P>0.05) feeding cost per kg gain was recorded in pigs supplemented with 2 % Azolla meal. Thus, it is concluded that supplementation of Azolla meal has positive effect on performance of crossbred grower and finisher pigs.